Development and Validation of Nomogram for the Prediction of Malignant Ventricular Arrhythmia Including Circulating Inflammatory Cells in Patients with Acute ST-Segment Elevation Myocardial Infarction - Wang L; Yang L; Li T; Geng S (Dove Medical Press, 2023)
Liang Wang, Liting Yang, Tao Li, Shanshan Geng Department of Cardiology, Shuyang Hospital of Traditional Chinese Medicine, Shuyang, Jiangsu, People's Republic of ChinaCorrespondence: Shanshan Geng, Department of Cardiology, Shuyang Hospital of Traditional Chinese Medicine, No. 28, Shanghai Road, Shuyang, Jiangsu, 223600, People's Republic of China, Tel + 86-052783562463, Email 1594743945@qq.comBackground: Malignant ventricular arrhythmia (MVA) can seriously affect the hemodynamic changes of the body. In this study, we developed and validated a nomogram to predict the in-hospital MVA risk in patients with STEMI after emergency PCI.Methods: The multivariable logistic regression analysis included variables with a P< 0.05 in the univariate logistic regression analysis and investigated the independent predictors affecting in-hospital MVA after PCI in patients with STEMI in the training cohort. The construction of a nomogram model used independent predictors to predict the risk of in-hospital MVA, and C-index, Hosmer-Lemeshow (HL) test, calibration curves, decision curve analysis (DCA), and receiver operating characteristic (ROC) were used to validate the nomogram.Results: Killip class [OR=5.034 (95% CI: 1.596- 15.809), P=0.005], CK-MB [OR=1.002 (95% CI: 1.001- 1.004), P=0.022], serum potassium [OR=0.618 (95% CI: 0.406- 0.918), P=0.020], NLR [OR=1.073 (95% CI: 1.034- 1.115), P< 0.001], and monocyte [OR=1.974 (95% CI: 1.376- 2.925), P< 0.001] were the independent predictors of in-hospital MVA after PCI in patients with STEMI. A nomogram including the 5 independent predictors was developed to predict the risk of in-hospital MVA. The C-index, equivalent to the area under the ROC curve (AUC), was 0.803 (95% confidence interval [CI]: 0.738- 0.868) in the training cohort, and 0.801 (95% CI:0.692- 0.911) in the validation cohort, showing that the nomogram had a good discrimination. The HL test (χ2=8.439, P=0.392 in the training cohort; χ2=9.730, P=0.285 in the validation cohort) revealed a good calibration. The DCA suggested an obvious clinical net benefit.Conclusion: Killip class, CK-MB, serum potassium, NLR, and monocyte were independent factors for in-hospital MVA after PCI in patients with STEMI. The nomogram model constructed based on the above factors to predict the risk of in-hospital MVA had satisfactory discrimination, calibration, and clinical effectiveness, and was an excellent tool for early prediction of the risk of in-hospital MVA after PCI in patients with STEMI.Keywords: ST-segment elevation myocardial infarction, percutaneous coronary intervention, nomogram model, malignant ventricular arrhythmia, circulating inflammatory cells